2007
DOI: 10.1109/tmm.2007.900138
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: Query by Semantic Example

Abstract: Abstract-A combination of query-by-visual-example (QBVE) and semantic retrieval (SR), denoted as query-by-semantic-example (QBSE), is proposed. Images are labeled with respect to a vocabulary of visual concepts, as is usual in SR. Each image is then represented by a vector, referred to as a semantic multinomial, of posterior concept probabilities. Retrieval is based on the query-by-example paradigm: the user provides a query image, for which 1) a semantic multinomial is computed and 2) matched to those in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(104 citation statements)
references
References 44 publications
2
97
0
2
Order By: Relevance
“…By exploiting the statistical structure of these ambiguities, a QBSE system is able to perform inferences at an higher level of abstraction, and significantly outperform QBVE systems. This has been confirmed by various recent studies, which have shown that QBSE systems can generalize much better than their QBVE counterparts [13].…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…By exploiting the statistical structure of these ambiguities, a QBSE system is able to perform inferences at an higher level of abstraction, and significantly outperform QBVE systems. This has been confirmed by various recent studies, which have shown that QBSE systems can generalize much better than their QBVE counterparts [13].…”
Section: Introductionsupporting
confidence: 68%
“…For brevity, we limit the discussion to the implementation details of contextual level. The visual and semantic levels are those proposed in [19] and [13], where they were shown to achieve better performance than a number of other state of the art image retrieval systems.…”
Section: Implementation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…While given a single video story learning the links between visual appearances of keyframes and speech transcript words is not possible, the concurrent occurrences in large number of available video stories provide that information learned, they can be used to predict labels for the regions (region labeling) as an alternative to large-scale object recognition. They can also be used in a setting similar to the query by semantic example method as proposed by [67].…”
Section: Linking Regions To Abstract In Annotated Keyframesmentioning
confidence: 99%